2009
DOI: 10.1002/hed.21113
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome for advanced‐stage supraglottic laryngeal cancer

Abstract: Regardless of index treatment, age over 60 years and clinical stage of the neck at presentation were the main independent predictors of OS and DSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 15 publications
2
30
2
4
Order By: Relevance
“…Multivariate analysis in supraglottic LSCC revealed that older age (>60 years), N2+ status and chemoradiotherapy were significant negative prognostic factors for OS, whereas T-status had no significant impact on outcomes. The negative impact of age and N+ status is consistent with the findings from Ganly et al [32], who investigated 182 cases of advanced-stage supraglottic LSCC treated at the Memorial Sloane-Kettering Cancer center. Contrary to the findings of Ganly et al , chemoradiotherapy showed a borderline negative associaton with OS in our cohort, whereas the remaining treatment modalities had no significant impact on the outcome.…”
Section: Discussionsupporting
confidence: 89%
“…Multivariate analysis in supraglottic LSCC revealed that older age (>60 years), N2+ status and chemoradiotherapy were significant negative prognostic factors for OS, whereas T-status had no significant impact on outcomes. The negative impact of age and N+ status is consistent with the findings from Ganly et al [32], who investigated 182 cases of advanced-stage supraglottic LSCC treated at the Memorial Sloane-Kettering Cancer center. Contrary to the findings of Ganly et al , chemoradiotherapy showed a borderline negative associaton with OS in our cohort, whereas the remaining treatment modalities had no significant impact on the outcome.…”
Section: Discussionsupporting
confidence: 89%
“…24,25 LFI for patients with T3 or T4 laryngeal cancer after RT or CRT was 77% or higher after 5 years. This finding is in agreement with the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Thus it is clear that the major advantages of radiotherapy or chemoradiotherapy for treatment of advanced laryngeal cancer are avoidance of an operation and anatomic preservation of the larynx, with no definite compromise in overall survival 14,43,44. On the other hand, the disadvantages include a high incidence of severe acute toxicity, and a high incidence of long-term laryngeal functional problems, particularly in patients treated with concurrent chemoradiotherapy 3538.…”
Section: Treatmentmentioning
confidence: 99%